Rethinking Durkheim and his tradition - Schmaus, Warren, 1952- (Cambridge University Press, 2004)
This book offers a major reassessment of the work of Emile Durkheim in the context of a French philosophical tradition that had seriously misinterpreted Kant by interpreting his theory of the categories as psychological faculties. Durkheim's sociological theory of the categories, as revealed by Warren Schmaus, is an attempt to provide an alternative way of understanding Kant. For Durkheim the categories are necessary conditions for human society. The concepts of causality, space and time underpin the moral rules and obligations that make society possible. A particularly original feature of this book is its transcendence of the distinction between intellectual and social history by placing Durkheim's work in the context of the French educational establishment of the Third Republic. It does this by subjecting student notes and philosophy textbooks to the same sort of critical analysis typically applied only to the classics of philosophy.